Managerial Ownership, Financial Performance, and Firm Size as Drivers of Company Value: Empirical Evidence from the Indonesian Food and Beverage Industry (2019–2023) - Gusti Ayu Kade Ita Maharani; Putu Novia Hapsari Ardianti (Philippine Social Science Journal, 2025)
This study examines the determinants of firm value (PBV) within Indonesia’s priority Food and Beverage sector, analyzing data from 20 companies listed on the Indonesia Stock Exchange between 2019 and 2023. By testing five internal factors, the research reveals that only leverage and Return on Assets (ROA) significantly enhance firm value, indicating that investors prioritize efficient asset profitability and strategic debt management over managerial ownership, liquidity, or firm size. These findings suggest that management should focus on optimizing external financing and operational efficiency, while future research should expand the scope to include macroeconomic variables and broader industrial comparisons.